Genetic diversity of salmonella enterica serovar paratyphi a from different geographical regions in Asia - Goh, Y.L.; Puthucheary, S.D.; Chaudhry, R.; Bhutta, Z.A.; Lesmana, M.; Oyofo, B.A.; Punjabi, N.H.; Ahmed, A.; Thong, Kwai Lin (Wiley, 2002)
Aims: Subtyping of Salmonella Paratyphi A isolates from India, Pakistan, Indonesia and Malaysia was carried out by pulsed-field gel electrophoresis (PFGE) to assess the extent of genetic diversity of these isolates from different endemic countries. Methods and Results: A total of 39 human isolates of Salmonella Paratyphi A from Pakistan, India, Indonesia and Malaysia were studied using PFGE analysis following digestion of chromosomal DNA with XbaI. Seven isolates from Pakistan were resistant to ampicillin, tetracycline and cotrimoxazole. It was noted that Salmonella Paratyphi A isolates obtained from outbreaks in India had limited genetic diversity and probably belonged to closely related clones. Significant genetic homogeneity was observed among antimicrobial-resistant isolates from Pakistan and antimicrobial-sensitive isolates from Pakistan and Indonesia, respectively. Conclusions: PFGE was a useful subtyping technique to differentiate Salmonella Paratyphi A from different endemic countries. However, it fails to differentiate the antimicrobial-resistant and -sensitive strains. Significance and Impact of the Study: The findings of the present study verify the usefulness of PFGE in characterizing and comparing strains of Salmonella Paratyphi A. Our study suggests that a limited number of clones are responsible for paratyphoid fever in these countries.